Hematological and blood chemistry parameters of a Podocnemis vogli and P. unifilis captive population in Colombia - Rodríguez-Almonacid, Cristian; Fuentes-Rodríguez, Gustavo; González, Leidy P.; Moreno-Torres, Carlos; Matta, Nubia E. (Frontiers in Veterinary Science, 2022)
The Podocnemididae family is seriously affected by anthropogenic factors, which is why almost all of their family members are threatened, according to the IUCN red list. The biology and ecology of these species, as well as the hematological and serum chemistry reference intervals that allow clinical action and decision-making conservation programs, are poorly known. Based on this, the objective of this study was to establish the hematological and blood chemistry parameters of the Savannah side-necked turtle (Podocnemis vogli) and Yellow-spotted river turtle (Podocnemis unifilis) maintained in captivity at the Estación de Biología Tropical Roberto Franco (Villavicencio-Colombia). Forty-nine captive turtles of the species P. vogli (n = 28) and P. unifilis (n = 21) were sampled to determine hematological and serum chemistry parameters. Blood samples were taken from the jugular veins of both male and female turtles across both species. Student's t-test and Mann–Whitney–Wilcoxon tests were used to compare values between the parameters evaluated against genders and sizes. Reference intervals were calculated for the hematological and biochemical values of each species. Some assessed parameters demonstrated significant differences between the males and females of both species. Most of the analyzed parameters exhibited similar reference intervals in both species. In this study, we report values and propose the hematological and serum chemistry reference intervals for P. vogli and P. unifilis, which can be used in the clinical diagnosis of these reptiles and in future research.